A comparison of contracting methods for bored pile (drilled shaft) construction between Europe and North America. Issue 2 (2nd July 2016) - Coleman, D. B.; Tipter, A.
Abstract : Delivery techniques involving conventional and non-conventional contracting methods in North America (NA) and Europe are presented for the construction of bored pile (drilled shaft) foundations. For the purpose of this paper, NA and European Specialty Foundation Contractors (SFCs) were polled through the Deep Foundations Institute (DFI) to determine common practices, issues, views and experiences facing the SFC during the installation of deep foundations. Additional information was compiled from research on the subject matter. Comparisons are provided pertaining to: contracting methods, document forms, payment, contracting provisions, regional influences and cultural differences involving language barriers and currency. In addition, the authors have considered and summarised the common aspects, trends and how the evolution of these methods has impacted or altered the North American/European SFC's business model. It should be noted that the authors' reference to NA refers to the United States, while Europe refers to members of the European Union, with emphasis on the United Kingdom and Germany.